The Dead Sea scrolls : transmission of traditions and production of texts - Metso, Sarianna. (Studies on the Texts of the Desert of Judah, 2010)
How were Jewish texts produced and transmitted in late antiquity? What role did scribal practices play in the shaping of both scriptural and interpretive traditions, which are-as the Scrolls show so decisively-intimately intertwined? How were texts assembled from a variety of earlier sources, both oral and written? Why were they often attributed to pseudonymous authors from the remote past such as Moses and David? How did the composers of these texts understand the enterprise in which they were engaged? This volume furthers current debates about Qumran Scribal Practice and the transmission of traditions in Jewish Antiquity. It is published with the conviction that the transmission of traditions and the details of scribal practices-so often treated separately-should be considered in conversation with each other.